In factors influence the sustainable of paddy production: A case of Tan Ah Boy Sdn Bhd - Lee, Ru Sheng; Wong, Xiao Hong; Ho, Mei Sing; Lim, Lay Xia; Teo, Teo Yi Min; Othman, Mohd Zainudin (2015)
This study focuses on the sustainable supply chain management of paddy in Malaysia.This study attempt to identify some problems related to collaboration at downstream of the supply chain such as weather, government, competitor, supply and demand. This study applied a quantitative approach. The data was collected by questionnaire.The respondents in this study are the all employees and the boss of Tan Ah Boy Sdn Bhd which are 10 respondents.All the questionnaires were returned as a final sample. The results show that all the variables have significant effect to the sustainable supply chain management of Tan Ah Boy Sdn Bhd especially the weather and government variables.